Doing as the elect do: Matthew 7:21 within Deuteronomistic and Matthean election theology - van den Os, Arjan (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
Matthew 7:21 is an exegetically challenging verse: it provides a complex formulation of Matthew’s election theology. Simultaneously, this text is systematically theologically challenging, due to its emphasis on doing the will of God. This article argues that Matthew 7:21 and Matthean election theology must be understood within the matrix of Deuteronomy and Deuteronomistic perspectives on election. Entrance into the kingdom of God is a divine gift, which finds fulfilment in Jesus Christ. This divine and incongruous gift, however, must be accompanied by doing the will of God. Faith is not merely a cognitive matter but also an active calling to be perfect (Mt 5:48). The recipients of this election can be identified primarily as the Jews, but in Christ, the circle of the divine family is extended to include the Gentiles. Matthew’s concept of election can thus be described as Christological, complex, consonant with the Old Testament, and ethically active. Contribution: By studying and contextualising Matthew’s election theology, this article contributes to a richer and more dynamic understanding of election in Reformed theology.